ELECTROMYOGRAPHIC EVALUATION OF THE EFFECTIVENESS OF ELECTROACUPUNCTURE IN EXPERIMENTAL DAMAGE OF NERVUS RADIALIS AND NERVUS ULNARIS IN RABBITS - Polat, Eren; Gunay, Cihan; Kavakli, Ahmet; Gonen, Murat (University of Belgrade, Faculty of Veterinary Medicine, 2023)
Many different acupuncture points and techniques have been used in the treatment of peripheral nerve injuries. It is known that alternative and complementary medicine techniques have become popular in the treatment of nerve damage in recent years. In this study, it was aimed to investigate the effectiveness of electroacupuncture in acute and chronic radial and ulnar nerve injuries. Electromyographic measurements were made to evaluate the effectiveness of electroacupuncture. In the study, the rabbits were divided into four groups namely acute nerve injury (ANI) group, chronic nerve injury (CNI) group, positive control (PC) group and negative control (NC) group. In the ANI, CNI and PC groups, damage was created on the nervus radialis and nervus ulnaris by applying pressure for 60 seconds using a hemostatic forceps under anesthesia. No damage was created in the NC group. Fifteen sessions of electroacupuncture were applied to the rabbits in the ANI, CNI, and NC groups every other day using LI-4, LI-10, LR-3, and ST-36 electroacupuncture points. Electroacupuncture was not applied to the rabbits in the PC group. Electromyographic examinations of both forelimbs of rabbits were performed during electroacupuncture applications. In the study, rabbits in the ANI group were measured at first amplitudes of 9.78 ± 1.66, and final amplitudes of 18.94 ± 1.83 (p ? 0.01). Rabbits in the CNI group were measured at first amplitudes of 11.34 ± 1.52, and final amplitudes of 16.03 ± 1.35 ( p ? 0.01). However, no statistically significant difference was found between the first and last latency values for both groups of rabbits. As a result, it was determined that electroacupuncture is an effective treatment method for both acute and chronic nerve injuries, as well as being more effective in acute cases than in chronic cases. © 2023 Polat et al. This is an open-access article distributed under the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited
ELEKTROMIOGRAFSKA PROCENA EFIKASNOSTI ELEKTROAKUPUNKTURE PRI EKSPERIMANTALNOM OŠTE?ENJU NERVUS RADIALIS I NERVUS ULNARIS KOD ZE?EVA
Keywords: electroacupuncture; electromyography; injury; nerve; rabbit